Raster-based Model for Mass Movement in Malang Regency, East Java, Indonesia. - Sandy Budi Wibowo; Franck Lavigne; Siddiq Luqman Rifai; Rani Rahim Suryandari; Idea Wening Nurani; St. Dwi Ermawan Danas Putra; Wahyu Widi Pamungkas (Journal of Geoscience, Engineering, Environment, and Technology, 2020)
Strengthening geospatial technology is very important in order to support disaster mitigation strategy, to manage vulnerable communities and to protectcritical environments. The main challenge in identifying disaster characteristics such as mass movements is the lack of direct observation during the event because it is too dangerous for researchers. Geo-Information Technology as a product of Geographic Information Science can be used as a solution in order to model the characteristics of mass movements. The purpose of this study is focused on identifying landslide processes from point of view ofraster-based model. The method of thisresearch emphasizes dynamic landslide model derived from timeseries raster calculation using MassMov2D algorithm. The geographic database that was built for spatial modeling comes from pedogeomorphological and Remote Sensing survey outputs, especially topographic data, landforms and soil physical properties. The result shows that the relationship between pixels (neighborhood) is determined by the topology of the energy gradient line direction which allowsto transfer the value between each pixel.The movement of landslide material starts from the toe. This decreases the stability of the landslide material in the main body of the landslide and generate progressive erosion.The raster-based model can finally reconstruct and identify the stages of initiation, transport and deposition landslide material.